Transition of Power : Britain's Loss of Global Pre-eminence to the United States, 1930±1945 - McKercher, B. J. C (Cambridge University, 2013)
This is a study of power. More particularly, it is a study of how power has been lost and won in international politics, of how Great Britain, the greatest of the great Powers in 1930, came to surrender its pre-eminence to the United States by the end of the Second World War. In this context, it shows how British leaders responded to the American question in their diplomacy; and why the British side of this relationship evolved as it did. What constitutes `power' is a vexed question.